Oral health profiles in the population of older adults in Ecuador: An analysis of latent classes - Adriana Canessa-Rojas; Marite Falquez-Flor; Stephanie Gallegos-Caamñano; Marco Faytong-Haro (PLoS ONE, 2025)
Background Ecuador’s aging population highlights the importance of addressing oral health issues among older adults because of the potential negative impact on their quality of life, nutrition, and overall well-being. Understanding the oral health profiles and specific needs of this population is crucial for the development of effective prevention and dental care strategies. This study aimed to identify and characterize the oral health profiles of older adults in Ecuador. Methods Data from the SABE 2009 survey were analyzed, encompassing responses from 5235 older adults from Ecuador. Oral health profiles were identified using oral health-related variables such as level of edentulism, the use of dentures, frequency of dental problems such as the change of food, among others. Additionally, a logistic regression analysis was conducted, in which sociodemographic and behavioral factors were assessed as predictors of the oral health profile membership of individuals. Results The analysis revealed 8 distinct oral health profiles among older Ecuadorian adults, varying in oral health status, prevalence of dental problems, and oral hygiene levels. Among these profiles, the three latent classes with the highest marginal probabilities were: (1) individuals with no original teeth, possessing complete dentures, minimal dental problems, and high satisfaction (0.22); (2) individuals with many missing teeth, dentures, minimal problems, and high satisfaction (0.19); and (3) individuals with all teeth missing, wearing dentures, with significant problems and high satisfaction (0.12). The significant factors influencing oral health status included age, education level, income, and access to dental services. Conclusion This study provides valuable insights into the diverse oral health profiles of older adults living in Ecuador. These findings can inform targeted prevention strategies and personalized dental care interventions to improve quality of life and overall well-being.